Sustainable methodical approaches to recycling sludge waste: value-added products, and their agricultural applications - Abas Siraj Hamda; Tesfaye Kassaw Bedru; Mani Jayakumar; Workisa Bacha Garuma (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: This review addresses the important global issue of increased sludge accumulation from wastewater treatment plants, which poses serious environmental challenges due to heavy metals and high levels of organic pollution. The study provides a thorough review of sludge-to-value-added product recovery methods, including anaerobic digestion, composting, vermicomposting, and pyrolysis.